Absolute frequency measurement of an Yb optical clock at the 10−16 level using International Atomic Time. (27th October 2020) - Luo, Limeng; Qiao, Hao; Ai, Di; Zhou, Min; Zhang, Shuang; Zhang, Sheng; Sun, Changyue; Qi, Qichao; Peng, Chengquan; Jin, Taoyun; Fang, Wei; Yang, Zhiqiang; et al.
Abstract: We report on the absolute frequency measurement of the 6 s 2 1 S 0 –6 s 6 p 3 P 0 transition in 171 Yb with a fractional uncertainty of 7.3 × 10 –16 . A global positioning system carrier phase frequency transfer was established between National Institute of Metrology of China and East China Normal University, which linked the optical frequency of the ECNU Yb1 clock to the second in the International System of Units (SI) through international atomic time. Frequency measurements were carried out in 15 separate days with a total time over 3.8 × 10 5 s. The absolute frequency was determined to be 518 295 836 590 863.30(38) Hz. Our result is in good agreement with the recommended value in neutral Yb as a secondary representation of the SI second endorsed by the International Committee for Weights and Measures.